Application of bentonite-loaded calcium-iron layered double hydroxides in passivating cadmium in tomato plants

By applying bentonite loaded with calcium-iron layered double hydroxide in cadmium-contaminated soil, the problem of difficult to passivate cadmium in tomato plants in cadmium-contaminated soil in the prior art is solved, and the effect of improving plant growth performance and reducing cadmium accumulation is achieved.

CN119552662APending Publication Date: 2025-03-04SHANDONG AGRICULTURAL UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411738601.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

The prior art is difficult to effectively passivate the cadmium in tomato plants planted in soil contaminated, resulting in the accumulation of cadmium poses a threat to plant growth and human health.

Method used

The material was prepared by co-precipitation method by using bentonite-loaded calcium-iron layered double hydroxide (CaFe-LDH@BT) as the repairing agent and applied to cadmium contaminated soil to improve the adsorption capacity of cadmium and reduce the accumulation of cadmium.

Benefits of technology

It significantly increases the fresh weight, dry weight, plant height and root length of tomato plants, and effectively reduces the cadmium content in the plants, reduces the transport and enrichment of cadmium, improves the cadmium morphology in the soil, thereby protecting plant health and environmental safety.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119552662A_ABST
    Figure CN119552662A_ABST
Patent Text Reader

Abstract

The invention discloses application of bentonite-loaded calcium-iron layered double hydroxides in passivating cadmium in tomato plants. The application comprises the following steps: increasing the fresh weight and dry weight of the tomato plants planted in cadmium-polluted soil; the plant height and root length of tomato plants planted in the cadmium-polluted soil are improved; and passivating cadmium in tomato plants planted in the cadmium-polluted soil. The bentonite-loaded calcium-iron layered double hydroxide is prepared by the following method: dissolving bentonite, FeCl3. 6H2O and CaCl2 in deionized water, adding Na2CO3 and NaOH solutions while stirring, adjusting the pH to 11-13 to obtain a solid-liquid mixture, filtering after reaction to obtain a precipitate, washing with deionized water to be neutral, drying and grinding to obtain the bentonite-loaded calcium-iron layered double hydroxide. The research aims at repairing Cd-polluted soil, bentonite and layered double hydroxides widely existing in the nature are used as raw materials, CaFe-LDH (at) BT is prepared by using a coprecipitation method, and the content of available Cd in the soil can be effectively reduced by applying 0.4% of CaFe-LDH (at) BT; the dry weight and fresh weight of tomato plants are improved, the content of Cd in roots, stems, leaves and fruits of the tomato plants is effectively reduced, and the transfer coefficient of Cd in the tomato plants and the enrichment coefficient of overground parts are also reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of cadmium passivation, and in particular to application of bentonite-loaded calcium-iron layered double hydroxide in cadmium passivation of tomato plants. Background Art

[0002] With the continuous advancement of the modernization process, all walks of life, especially mining, electroplating, alloy manufacturing and other industries, are constantly developing, and the scale of production is constantly increasing. More and more heavy metals are also continuously discharged into the environment with the progress of production activities. The problem of heavy metal pollution has become increasingly serious, and heavy metal elements such as Cd have become common pollution. Cd has no known biological function in the human body, but compared with other heavy metal elements, it has the highest accumulation rate. It is also a non-essential, highly soluble, and non-degradable element, mainly present in the soil. The problem of soil pollution is not only an ecological and environmental problem, but also a major problem involving life and health. Once the soil for growing grain and vegetables is contaminated by heavy metals, it will enter the human body through the crops planted on it, causing damage to human health. Unlike general pollution, heavy metal pollution is colorless and odorless, so it is difficult for people to directly perceive it through human senses. It is generally absorbed by plants in the soil and accumulates to a certain extent through the food chain before it appears. Therefore, heavy metal pollution has a strong concealment and hysteresis, which is more difficult to be discovered than ordinary pollution, and it also needs to attract more attention from people.

[0003] Layered double hydroxides (LDH S ), also known as hydrotalcite, is a type of anionic clay compound with large specific surface area, the ability to adsorb other substances, easy preparation, and low cost. Therefore, it can be used as a soil remediation agent. Due to its special structure and unique physical and chemical properties, layered double hydroxides have received more and more attention in the field of environmental remediation in recent years, especially in the removal of heavy metals from water and soil. Layered double hydroxides are simple to prepare and low in cost. They are an adsorbent that can effectively adsorb heavy metal ions. However, due to the original LDH S There are defects such as easy aggregation, low production capacity, difficult regeneration process, lack of functional groups and structural components, which limit its adsorption capacity and further application, resulting in its inability to fully exert its due application value. Therefore, functionalized LDH is prepared by artificially synthesizing layered hydroxide composite materials and adding new functional groups and structural components to them. S It has become one of the common application methods. Bentonite is a natural mineral with low price, abundant reserves, and can be found almost all over the world. Bentonite has a large specific surface area, so it has good adsorption capacity for pollutants such as heavy metals. The addition of bentonite can effectively reduce LDH SThe accumulation of LDH increases its specific surface area and porosity, thereby effectively improving S Adsorption capacity for heavy metal ions.

[0004] Patent CN118374286A discloses a modified rice straw biochar for repairing cadmium-contaminated rice fields and its preparation method. It uses magnesium-iron layered double hydroxide modified biochar Mg-Fe LDH@RSBC to repair nuclear contaminated rice fields, which can reduce the effective Cd in the soil, reduce the absorption of Cd in the soil by rice plants, and at the same time reduce the total Cd content in the soil and increase the total Mg and total Fe content in the soil. Kong et al. (2021) used CaAl-LDH as an amendment to stabilize the mineralization of Cd in agricultural soil, and its fixation efficiency in the soil reached 96.9% within 28 days. It was then applied to 10 hectares of fields in Jiangsu Province, China for three years. In the first year after application, the Cd content in wheat grains was lower than 0.1 mg / kg specified in the Chinese Food Safety Standard (GB2762-2022). Although there have been many reports on the use of layered double hydroxides to passivate cadmium in soil in the prior art, there are few reports on the passivation of cadmium in tomato plants grown in cadmium-contaminated soil. Summary of the invention

[0005] In view of the above prior art, the purpose of the present invention is to provide the application of bentonite-loaded calcium iron layered double hydroxide in passivating cadmium in tomato plants.

[0006] To achieve the above object, the present invention adopts the following technical solution:

[0007] The first aspect of the present invention provides the use of bentonite-supported calcium iron layered double hydroxide in at least one of the following (1)-(3):

[0008] (1) Increase the fresh weight and dry weight of tomato plants grown in cadmium-contaminated soil;

[0009] (2) Increase plant height and root length of tomato plants grown in cadmium-contaminated soil;

[0010] (3) Passivation of cadmium in tomato plants grown in cadmium-contaminated soil.

[0011] The bentonite-loaded calcium iron layered double hydroxide is prepared by the following method:

[0012] Bentonite, FeCl 3 6H 2 O and CaCl 2 Dissolve in deionized water and add Na 2 CO 3and NaOH solution, adjusting the pH to 11-13 to obtain a solid-liquid mixture, filtering to obtain a precipitate after the reaction, washing with deionized water to neutrality, drying, and grinding to obtain bentonite-loaded calcium iron layered double hydroxide.

[0013] Preferably, the passivation of cadmium in tomato plants grown in cadmium-contaminated soil specifically involves reducing the cadmium content in roots, stems, leaves and fruits of tomato plants grown in cadmium-contaminated soil.

[0014] As a preferred embodiment, bentonite, FeCl 3 6H 2 O, CaCl 2 The ratio of the amount of water added is (3-5) g: (0.02-0.04) mol: (0.10-0.15) mol: (250-350) mL.

[0015] Preferably, Na 2 CO 3 The concentrations of the NaOH solutions are both 0.4-0.6 mol / L.

[0016] Preferably, Na 2 CO 3 The volume ratio of HCl to NaOH solution is 1:2-4.

[0017] Preferably, the reaction temperature is 70-90°C and the reaction time is 16-20h.

[0018] As a preferred embodiment, the specific method of application is:

[0019] The bentonite-loaded calcium iron layered double hydroxide is applied to cadmium-contaminated soil for passivation treatment, and the application amount is 3-5 g of bentonite-loaded calcium iron layered double hydroxide per kilogram of soil.

[0020] Beneficial effects of the present invention:

[0021] 1. This study aims to repair soil contaminated by Cd. Using bentonite and layered double hydroxides widely found in nature as raw materials, bentonite-loaded calcium iron layered double hydroxide (CaFe-LDH@BT) was prepared by coprecipitation. The results of SEM showed that the CaFe-LDH@BT prepared in this study had layered structures and flower-like aggregates. The appearance of these structures increased its specific surface area and provided more adsorption sites. BET analysis showed that the specific surface area of ​​CaFe-LDH@BT was 131.08 m 2 / g, the specific surface area is increased by 92.93% compared with BT.

[0022] 2. The results of the adsorption kinetics and isothermal adsorption tests of CaFe-LDH@BT showed that the adsorption amount and adsorption rate of Cd(Ⅱ) by CaFe-LDH@BT obtained after BT was loaded with CaFe-LDH were significantly improved, and the adsorption amount of Cd(Ⅱ) could reach 117.13 mg / g within 300 min.

[0023] 3. The application of CaFe-LDH@BT can reduce the content of effective Cd in the soil and convert it into a low-activity form, thereby reducing the accumulation of Cd in tomato plants. The experimental results of this study showed that the treatment group with 0.4% CaFe-LDH@BT addition can significantly increase the fresh weight and dry weight of the aboveground part of tomato plants, and increase the plant height and root length of tomatoes. The application of CaFe-LDH@BT effectively reduced the content of Cd in the roots, stems, leaves and fruits of tomato plants, and the Cd transport coefficient and aboveground enrichment coefficient in tomato plants were also reduced. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 : Scanning electron microscopy images of BT (a) and CaFe-LDH@BT (b);

[0025] Figure 2 : EDS split-mirror image of CaFe-LDH@BT (a) and EDS spectrum of CaFe-LDH@BT: O element (b), Al element (c), Si element (d), Ca element (e), Fe element (f);

[0026] Figure 3 :N of BT(a) and CaFe-LDH@BT(b) 2 Adsorption-desorption isotherms;

[0027] Figure 4 :XRD spectra of BT and CaFe-LDH@BT;

[0028] Figure 5 :FT-IR spectra of BT, CaFe-LDH@BT and CaFe-LDH@BT after adsorption of Cd(Ⅱ)

[0029] Figure 6 :XPS spectra of CaFe-LDH@BT before and after adsorption of Cd(Ⅱ); (a) Overall spectrum of CaFe-LDH@BT before and after adsorption of Cd(II); (b) Cd3d spectrum; (c) C1s spectrum; (d) O1s spectrum; (e) Ca2p spectrum; (f) Fe2p spectrum;

[0030] Figure 7:Pseudo-first-order and pseudo-second-order kinetic models for the adsorption of Cd(Ⅱ) by CaFe-LDH@BT; (a) Kinetic curve and model fitting of the adsorption process of Cd(Ⅱ) by BT; (b) Kinetic curve and model fitting of the adsorption process of Cd(Ⅱ) by CaFe-LDH@BT;

[0031] Figure 8 :Adsorption isotherms of BT and CaFe-LDH@BT for Cd(Ⅱ);

[0032] Fig. 9 :Effects of different application rates of BT and CaFe-LDH@BT on bioavailable Cd in soil;

[0033] Fig.10 :Effects of different application rates of BT and CaFe-LDH@BT on the Cd occurrence forms in soil at 7, 14, 30, 60 and 100 days;

[0034] Fig.11 : Fresh weight of above-ground (a) and underground (b) parts of tomato plants in different treatment groups;

[0035] Fig.12 : Dry weight of above-ground (a) and underground (b) parts of eggplant plants in different treatment groups;

[0036] Fig.13 :Plant height (a) and root length (b) of tomato plants in different treatment groups

[0037] Fig.14 : Cd contents in roots (a), stems (b), leaves (c) and fruits (d) of tomato plants in different treatment groups. DETAILED DESCRIPTION

[0038] It should be noted that the following detailed descriptions are illustrative and are intended to provide further explanation of the present application. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those commonly understood by those skilled in the art to which the present application belongs.

[0039] In order to enable those skilled in the art to more clearly understand the technical solution of the present application, the technical solution of the present application will be described in detail below in conjunction with specific embodiments.

[0040] The test materials used in the examples of the present invention are all conventional test materials in the art and can be purchased through commercial channels.

[0041] The bentonite used in the following examples and comparative examples of the present invention is sodium bentonite, which was purchased from Roan Reagent Co., Ltd.

[0042] Example 1: Preparation of bentonite-loaded calcium iron layered double hydroxide:

[0043] 4g bentonite, 0.03mol FeCl 3· 6H 2 O and 0.12 mol CaCl 2 Dissolve in 300 mL of deionized water and add 0.5 mol / L of Na 2 CO 3 solution and 0.5 mol / L NaOH solution, Na 2 CO 3 The volume ratio of the aqueous solution to the NaOH solution is 1:3, and the pH is adjusted to about 12 to obtain a solid-liquid mixture, which is then reacted in an oven at 80°C for 18 hours. After the reaction, the precipitate is filtered to obtain a precipitate, which is washed with deionized water to neutrality, dried, and ground to obtain bentonite-loaded calcium iron layered double hydroxide, recorded as CaFe-LDH@BT.

[0044] Embodiment 2:

[0045] 3g bentonite, 0.02mol FeCl 3· 6H 2 O and 0.10 mol CaCl 2 Dissolve in 300 mL of deionized water and add 0.5 mol / L of Na 2 CO 3 solution and 0.5 mol / L NaOH solution, Na 2 CO 3 The volume ratio of the aqueous solution to the NaOH solution is 1:3, the pH is adjusted to about 12 to obtain a solid-liquid mixture, and then the solid-liquid mixture is reacted in an oven at 80°C for 18 hours. After the reaction, the precipitate is filtered to obtain a precipitate, and the precipitate is washed with deionized water to neutrality, dried, and ground to obtain bentonite-loaded calcium iron layered double hydroxide.

[0046] Embodiment 3:

[0047] 5g bentonite, 0.04mol FeCl 3· 6H 2 O and 0.15 mol CaCl 2 Dissolve in 300 mL of deionized water and add 0.5 mol / L of Na 2 CO 3 solution and 0.5 mol / L NaOH solution, Na 2 CO 3The volume ratio of the aqueous solution to the NaOH solution is 1:3, the pH is adjusted to about 12 to obtain a solid-liquid mixture, and then the solid-liquid mixture is reacted in an oven at 80°C for 18 hours. After the reaction, the precipitate is filtered to obtain a precipitate, and the precipitate is washed with deionized water to neutrality, dried, and ground to obtain bentonite-loaded calcium iron layered double hydroxide.

[0048] Test example:

[0049] Bentonite (BT) and CaFe-LDH@BT prepared in Example 1 were characterized by SEM, BET, XRD, FT-IR and XPS.

[0050] 1. Scanning Electron Microscope (SEM)

[0051] The samples were directly glued onto the conductive adhesive and sprayed with gold using a German ZEISS Sigma 300 scanning electron microscope to observe the microstructures of BT and CaFe-LDH@BT.

[0052] The morphology and microstructure of BT and CaFe-LDH@BT were observed using scanning electron microscopy. Figure 1 As shown, the EDS split-mirror image is as follows Figure 2 shown.

[0053] Depend on Figure 1 As shown in (a), BT is mostly blocky, with a rough surface and large particles with irregular shapes, which are prone to Figure 1 The agglomeration phenomenon in (a-1) reduces its specific surface area and is not conducive to the adsorption of heavy metals. Figure 1 (b-1) shows that the CaFe-LDH@BT synthesized by coprecipitation in this study has a layered structure. Figure 1 (b-2) and (b-3) show that CaFe-LDH@BT has flower-shaped aggregates stacked upward, exposing more adsorption sites. In addition, the layered structure further increases its specific surface area and has more pores, which is conducive to adsorption and reduces the occurrence of agglomeration.

[0054] Figure 1 (a-2) and (a-3) show that the adsorption sites of BT are not fully exposed. Figure 1 The morphology and structure of BT are vaguely visible in (b-1). Figure 1 (b-2) shows more adsorption sites.

[0055] Depend on Figure 2From the EDS split-mirror image and EDS spectrum of CaFe-LDH@BT (d), it can be seen that O, Al, Si, Ca, and Fe elements are evenly distributed on the surface of CaFe-LDH@BT, among which Al and Si elements unique to BT are also evenly distributed on the surface, indicating that CaFe-LDH is successfully and evenly loaded on BT, which is consistent with the SEM image of CaFe-LDH@BT.

[0056] 2. Specific surface area and pore size distribution test (BET)

[0057] The American Micromeritics ASAP2460 fully automatic specific surface area and porosity analyzer was used. 2 The specific surface area, average pore size and pore volume of BT and CaFe-LDH@BT were determined by adsorption-desorption.

[0058] The specific surface area, pore size and pore capacity of BT and CaFe-LDH@BT were tested as follows: Figure 3 As shown in Table 1.

[0059] Table 1 Performance indicators of BT and CaFe-LDH@BT

[0060]

[0061] Using N 2 Adsorption-desorption tests of BT and CaFe-LDH@BT were conducted. The test results showed that the gas adsorption-desorption isotherms of the two materials conformed to the IV type adsorption isotherm under the IUPAC classification standard, and there was an obvious H3 hysteresis loop, indicating that both BT and CaFe-LDH@BT were mesoporous adsorption materials. The analysis results of the performance indicators of the two materials showed that the specific surface area of ​​BT was 67.94m 2 / g, the specific surface area of ​​CaFe-LDH@BT is 131.08m 2 / g, the specific surface area of ​​CaFe-LDH@BT increased by 92.93%, becoming 1.93 times of the original. The average pore size and pore capacity of CaFe-LDH@BT decreased compared with BT, which may be due to the fact that CaFe-LDH filled the pores of BT after loading.

[0062] 3. X-ray diffraction (XRD)

[0063] The phase composition and crystal structure of BT and CaFe-LDH@BT were determined by a Japanese Rigaku Ultima IV X-ray diffraction analyzer with a scanning range of 10 to 90° and a scanning speed of 2° / min.

[0064] like Figure 4As shown in the figure, BT and CaFe-LDH@BT have similar physical phases. For the original BT, its XRD results include the diffraction peaks of montmorillonite corresponding to the (001), (020), (101) and (200) crystal planes, and almost all the obvious diffraction peaks in the sample belong to the diffraction peaks of montmorillonite. In addition, the diffraction peaks of montmorillonite in the diffraction spectrum are relatively sharp, indicating a high degree of order and good crystallinity. After loading CaFe-LDH, the characteristic diffraction peak at 29.2° corresponds to the (110) crystal plane in the CaFe-LDH material. At the same time, the XRD results of the composite material include the characteristic peaks of the original BT material at 35°~50°, indicating that CaFe-LDH has been successfully loaded on BT, which is consistent with the results obtained when the microscopic morphology of CaFe-LDH@BT was observed using a scanning electron microscope.

[0065] 4. Fourier transform infrared spectroscopy (FT-IR)

[0066] The surface functional groups of BT and CaFeLDH@BT were analyzed by the KBr tablet method using a ThermoScientific Nicoleti S20 Fourier transform infrared spectrometer from the United States. The wavenumber range was 4000-400 cm -1 .

[0067] Fourier transform infrared spectra of BT and CaFe-LDH@BT before and after adsorption of Cd(Ⅱ) are shown in Figure 2. Figure 5 shown.

[0068] like Figure 5 As shown in the figure, the infrared spectra of BT and CaFe-LDH@BT are similar, indicating that the basic structure of BT has not changed due to the loading of CaFe-LDH. -1 With 3629cm -1 The absorption peaks at 1451 cm-1 are the stretching vibration peaks of the hydroxyl group and HOH, respectively. -1 The absorption peak at is caused by CO 3 2- Successfully inserted into the interlayer of CaFe-LDH, resulting in 465cm -1 The absorption peak at 519 cm belongs to the bending vibration peak of Si-O-Al. -1 The absorption peak at 875 cm is caused by the bending vibration of Si-O-Mg. -1 The absorption peak at is due to CaCO 3 CaFe-LDH@BT at 465cm -1The absorption peak at 1034cm is lower than that of BT and is relatively gentle. Studies have shown that this may be caused by the stretching vibration of MO (M: Ca or Fe) in the lattice. -1 The absorption peak at 465cm belongs to the Si-O-Si vibration peak. Both BT and CaFe-LDH@BT have this absorption peak, which indicates that the functional groups of BT still exist in CaFe-LDH@BT and CaFe-LDH is successfully loaded on the BT surface. -1 、519cm -1 and 875cm -1 The absorption peak of metal oxide at 3383 cm -1 The stretching vibration peaks of the hydroxyl groups at the positions were all weakened, indicating that these functional groups were involved in the adsorption process of Cd(Ⅱ).

[0069] 5. X-ray Photoelectron Spectroscopy (XPS)

[0070] The electronic state and elemental composition of CaFe-LDH@BT before and after adsorption of Cd(Ⅱ) were determined by the American ThermoScientific ESCALAB250Xi X-ray photoelectron spectrometer. The sample was fixed on the sample stage with conductive glue for sample preparation, and an Al target was used for measurement. The working voltage was 12.5 kV, and the charge correction was performed with C1s=284.80 eV binding energy as the energy standard.

[0071] Figure 6 (a) is the overall spectrum of CaFe-LDH@BT before and after adsorption of Cd(Ⅱ). The Ca2p peak appears at around 348eV and the Fe2p peak appears at around 710eV. In addition, the Si2p and Al2p peaks of Si and Al elements unique to BT also appear at around 101eV and 74eV, which again shows that CaFe-LDH has been successfully loaded onto BT. After CaFe-LDH@BT adsorbs Cd(Ⅱ), not only the original C1s, O1s, Ca2p and Fe2p peaks are retained, but also a new Cd3d diffraction peak appears, proving that Cd(Ⅱ) has been successfully adsorbed on the surface of CaFe-LDH@BT. Figure 6 The peaks at 412.0 eV and 405.2 eV in (b) correspond to Cd3d 3 / 2 and Cd3d 5 / 2 Characteristic peak. Figure 6From the energy spectrum of C1s before and after adsorption of Cd(Ⅱ) in (c), it can be seen that the characteristic peaks at 288.9 eV, 286.2 eV, and 284.8 eV correspond to the vibration stretching of C-OOH, C-OH, and CC, respectively. After the adsorption of Cd(II), the peaks at 288.9 eV and 286.2 eV showed a slight shift, and the peak areas of the three peaks changed to a certain extent, indicating that C-OOH, C-OH, and CC all participated in the adsorption process of Cd(Ⅱ). Figure 6 (d) is the O1s spectrum before and after the reaction. The three peaks at 536.2 eV, 531.7 eV, and 529.8 eV correspond to H 2 The characteristic peaks of O, C=O and lattice oxygen (FeO / Ca-O) shifted slightly at 531.7eV and 529.8eV after the adsorption of Cd(Ⅱ), and the peak areas at the two locations also changed, indicating that both the hydroxyl group and the lattice oxygen participated in the adsorption process of Cd(Ⅱ). Figure 6 As shown in (e), 349.7eV and 346eV correspond to Ca2p 1 / 2 Ca2p 3 / 2 The characteristic peaks of Ca(Ⅱ) have a slight change in the position and area of ​​the two peaks after adsorption of Cd(Ⅱ). 2+ involved in the adsorption process. Figure 6 (f) Around 725eV is Fe2p 3 / 2 The characteristic peak of Fe2p is around 711eV 1 / 2 The characteristic peaks of Fe are at 732.2eV and 719.3eV, which are satellite peaks, and 724.1eV and 710.5eV, which are corresponding to Fe 2+ The characteristic peaks of Fe at 726.3eV and 712.5eV 3+ The characteristic peak of Fe is shown in Table 1. 2+ The proportion of Fe 3+ The proportion of Fe increased from 35.37% to 38.62% after adsorption, indicating that part of Fe 2+ Oxidized to Fe 3+ Therefore, redox reaction is an important mechanism in the adsorption of Cd(Ⅱ) by CaFe-LDH@BT.

[0072] Test Example 1: Adsorption test:

[0073] In order to study the adsorption performance of CaFe-LDH@BT for Cd(Ⅱ), the adsorption mechanism of CaFe-LDH@BT for Cd(Ⅱ) in aqueous solution was studied by adsorption kinetics and adsorption isotherms.

[0074] 1. Test method:

[0075] 1.1 Adsorption kinetics test:

[0076] Weigh 0.02 g of BT and CaFe-LDH@BT prepared in Example 1 into a 50 mL centrifuge tube, add 20 mL of 50 mg / L Cd 2+ The solution was filtered through a 0.45 μm pore size water filter membrane into a 10 mL centrifuge tube, and the Cd(Ⅱ) content in the filtrate was determined by ICP-OES.

[0077] The calculation formulas for the adsorption amount Qe and removal rate of Cd(Ⅱ) by CaFe-LDH@BT are:

[0078]

[0079] Where: Q e ——Adsorption amount of Cd(Ⅱ) ions, mg / g;

[0080] C 0 ——initial concentration of Cd(Ⅱ) ions, mg / L;

[0081] C e ——Equilibrium concentration of Cd(Ⅱ) ions, mg / L;

[0082] V——volume of solution, L;

[0083] m——material dosage, g;

[0084] P——Cd(Ⅱ) removal rate, %.

[0085] (1) Pseudo-first-order kinetic model:

[0086] It mainly describes the physical adsorption process, and its nonlinear expression is:

[0087] ln(Q e -Q t )=lnQ e -K 1 ·t

[0088] Where: Q t ——The adsorption amount at the adsorption time t, mg / g;

[0089] Q e ——adsorption amount at adsorption equilibrium, mg / g;

[0090] k 1——Rate constant of pseudo-first-order kinetic model, min -1 ;

[0091] t——time, min.

[0092] (2) Pseudo-second-order kinetic model

[0093] It mainly describes the chemical adsorption process, and its nonlinear expression is:

[0094]

[0095] Where: Q t ——The adsorption amount at the adsorption time t, mg / g;

[0096] Q e ——adsorption amount at adsorption equilibrium, mg / g;

[0097] k 2 ——Rate constant of pseudo-second-order kinetic model, g / (mg·min);

[0098] t——time, min.

[0099] 1.2 Isothermal adsorption test:

[0100] Weigh 0.02 g of BT and CaFe-LDH@BT prepared in Example 1 in a 50 mL centrifuge tube, add 20 mL of 50 mg / L Cd(Ⅱ) solution, set a time gradient of 5, 10, 20, 30, 60, 120, 180, 240, 360, 540, and 720 min, shake at 180 rpm at 25 °C and take samples, with 3 parallels set for each group, filter through a 0.45 μm pore size water filter membrane into a 10 mL centrifuge tube, and determine the Cd(Ⅱ) content in the filtrate by ICP-OES.

[0101] (1) Langmuir isotherm adsorption model

[0102] Assuming that the material has uniform adsorption sites and the adsorption mode is monolayer adsorption, the expression of the model is:

[0103]

[0104] Where: Q e ——Equilibrium adsorption amount at adsorption equilibrium, mg / g;

[0105] Q max ——Theoretically, the maximum adsorption capacity of the material for Cd(Ⅱ); mg / g;

[0106] K L ——Langmuir model constant, L / mg;

[0107] C e ——The concentration of Cd(Ⅱ) in the solution at adsorption equilibrium, mg / L.

[0108] (2) Freundlich isotherm adsorption model:

[0109]

[0110] Where: Q e ——Equilibrium adsorption amount at adsorption equilibrium, mg / g;

[0111] K f ——Freundlich adsorption constant, mg / g;

[0112] C e ——Equilibrium concentration of Cd(Ⅱ) solution, mg / L;

[0113] n——adsorption intensity constant.

[0114] 2. Test results:

[0115] 2.1 Adsorption kinetics test results:

[0116] Table 2 Adsorption kinetic model parameters

[0117]

[0118] The pseudo-first-order and pseudo-second-order kinetic models for the adsorption of Cd(Ⅱ) by CaFe-LDH@BT are shown in Figure 2. Figure 7 The relevant fitting parameters are shown in Table 2.

[0119] like Figure 7 As shown in Table 2, in the first 120 min, the adsorption of Cd(Ⅱ) by BT and CaFe-LDH@BT increased rapidly, indicating that a large amount of Cd(Ⅱ) combined with the adsorption sites on CaFe-LDH@BT. As time went on, the rate of increase in the adsorption gradually slowed down, which may be due to the saturation of the adsorption sites on CaFe-LDH@BT. Finally, at about 300 min, BT and CaFe-LDH@BT reached adsorption equilibrium. The process of BT adsorption of Cd(Ⅱ) fits better with the pseudo-second-order kinetics, and the correlation coefficient (R 2 =0.9803) is greater than the correlation coefficient (R 2=0.9540), indicating that its adsorption process is mainly chemical adsorption; the theoretical equilibrium adsorption capacity of Cd(Ⅱ) is 31.88 mg / g, which is consistent with the actual adsorption capacity of 34.57 mg / g in 100 mg / LCd(Ⅱ) solution. The adsorption capacity of CaFe-LDH@BT for Cd(Ⅱ) is 117.13 mg / g, which is consistent with the theoretical maximum adsorption capacity of 116.40 mg / g. The correlation coefficient (R 2 =0.9995) is better than the pseudo-second-order kinetic model (R 2 =0.9273), indicating that the adsorption process is mainly physical adsorption. In addition, in a 100 mg / L Cd(Ⅱ) solution, the adsorption capacity of CaFe-LDH@BT for Cd(Ⅱ) is 3.39 times that of BT for Cd(Ⅱ), indicating that the loading of CaFe-LDH significantly improves the adsorption capacity of BT for Cd(Ⅱ).

[0120] 2.2 Isothermal adsorption test results:

[0121] Table 3 Adsorption isotherm model parameters

[0122]

[0123] Depend on Figure 8 As shown in Table 3, with the increase of Cd(Ⅱ) concentration, the adsorption amount of Cd(Ⅱ) by BT and CaFe-LDH@BT gradually increased, which was caused by the increasing concentration gradient. As the concentration of Cd(Ⅱ) further increased, the adsorption amount of Cd(Ⅱ) by BT and CaFe-LDH@BT gradually slowed down, which may be due to the saturation of the adsorption sites. Under the conditions of different Cd(Ⅱ) concentrations, the adsorption capacity of CaFe-LDH@BT for Cd(II) was significantly improved compared with BT. By comparing the theoretical and actual saturated adsorption capacities, it can be seen that the fitted adsorption capacity of BT and CaFe-LDH@BT for Cd(Ⅱ) is close to the measured adsorption capacity. In addition, the correlation coefficient (R 2 =0.8779, 0.9507) are both larger than the Freundlich isotherm adsorption model (R 2

[0124] =0.8571, 0.8888), indicating that the Langmuir isotherm adsorption model can better describe the adsorption process, and the adsorption of Cd(Ⅱ) by both belongs to monolayer adsorption. In the relevant parameters of the Freundlich model, when n<1, it means that the adsorbent is uniformly adsorbed, and when n>1, it shows non-uniform adsorption. From the fitting results in Table 3, it can be seen that the adsorption of Cd(Ⅱ) by BT and CaFe-LDH@BT belongs to non-uniform adsorption.

[0125] Test example 2: Potted plant test:

[0126] 1. Test method:

[0127] A pot experiment was designed to study the passivation ability of CaFe-LDH@BT on Cd in soil. 1.0 kg of soil (cadmium content was 3.86 mg / kg) that was sieved through a 10-mesh sieve after being air-dried after equilibrium contamination was added to a flowerpot. Different amounts (2.0, 4.0, 8.0, 15.0 g) of CaFe-LDH@BT and 0.4% (4.0 g) of bentonite were added according to the ratio of material: soil (mass percentage) = 0.2%, 0.4%, 0.8%, and 1.5%, respectively. After being fully mixed, the mixture was added to the flowerpot. The bottom of the pot was padded with gauze to prevent leakage. The control group was not applied with any material. Three parallels were set up in each group, with a total of 18 potted plants, and dwarf red tomato seedlings were planted in the pots.

[0128] The treatment groups were:

[0129] (1) Control group CK without any treatment;

[0130] (2) Treatment F0.2% with CaFe-LDH@BT addition of 0.2%;

[0131] (3) Treatment F0.4% with CaFe-LDH@BT addition of 0.4%;

[0132] (4) Treatment F0.8% with CaFe-LDH@BT addition of 0.8%;

[0133] (5) Treatment F1.5% with CaFe-LDH@BT addition of 1.5%;

[0134] (6) The treatment group with 0.4% bentonite addition: BT0.4%.

[0135] The soil in the potted plants was sampled at 7, 14, 30, 60, and 100 days, and the content of available cadmium and the content of different forms of cadmium in the soil at each period were determined. The plants were harvested 100 days after planting, and the aboveground and underground parts were separated, rinsed with deionized water, dried with absorbent paper, and the plant height and root length were measured, and the fresh weight of the plants was weighed. The various parts of the plants after weighing the fresh weight were dried, fixed at 105°C for 30 minutes, and then dried at 70°C to constant weight, and the dry weight of each part was weighed. After that, the plant samples of each part were ground, and the Cd content in the roots, stems, leaves, and fruits was determined respectively.

[0136] 2. Test indicators:

[0137] 2.1 Determination of total Cd and available Cd in soil:

[0138] The total Cd extraction in the soil was determined according to the method HJ803-2016 "Determination of 12 metal elements in soil and sediment by aqua regia extraction-inductively coupled plasma mass spectrometry".

[0139] 2.2 Determination of BCR Cd content in soil:

[0140] The forms of Cd in soil are divided into four forms: weak acid extraction state, reducible state, oxidizable state and residual state. The improved BCR four-step extraction method is used to extract Cd in different forms. The specific extraction steps are shown in the following table:

[0141] Table 4 BCR four-step extraction method

[0142]

[0143] The calculation formula for determining the content of different forms of Cd in soil by the BCR four-step extraction method is:

[0144] Where: w——the content of a certain form of Cd in the soil in the four-step extraction method, mg / kg;

[0145] c——the concentration of a certain form of Cd in the soil of the sample, mg / L;

[0146] v——volume of the solution when constant volume is reached, mL;

[0147] m——The mass of the soil sample after sieving, g.

[0148] 2.3 Determination of Cd content in different parts of tomato plants:

[0149] After drying the roots, stems, leaves, and fruits of the plants, 0.2 g of plant samples were weighed into 100 mL conical flasks and digested with concentrated nitric acid and perchloric acid (4:1) on a 180 °C hot plate until the solution turned white. 3The solution was used to wash the conical flask and make up the volume. After passing through a 0.45 μm water filter membrane, the Cd content in the sample was determined by ICP-OES.

[0150] The calculation method of Cd content in plants is:

[0151]

[0152] Where: w——Cd content in plant samples, mg / kg;

[0153] c——the concentration of Cd in the sample, mg / L;

[0154] v——volume of the solution when constant volume is reached, mL;

[0155] m——the mass of the plant sample, g.

[0156] 2.4 Calculation of bioconcentration coefficient and transport coefficient:

[0157]

[0158] In this study, Microsoft Excel 2021, IBM SPSS Statistics 26 and Origin 2018 were used to process the experimental data and draw charts. The significance of the differences between the data was tested using Duncan's new multiple range method (P<0.05).

[0159] 3. Test results:

[0160] 3.1 Effect of CaFe-LDH@BT on the biologically available state of Cd in soil:

[0161] The toxicity and biological activity of heavy metals are not only related to their total amount in the soil, but also closely related to their biologically effective state. The biologically effective Cd in the soil is the part that can be absorbed and utilized by organisms, which will affect the migration, enrichment, toxicity and biological effects of Cd in the soil. The higher the effective state content, the higher its bioavailability. Therefore, this experiment compared and analyzed the changes in the effective Cd content in the soil after applying different dosages of CaFe-LDH@BT (0.2%, 0.4%, 0.8%, 1.5%) and BT (0.4%) to Cd-contaminated soil for 7, 14, 30, 60 and 100 days. CK is the blank control group without added materials.

[0162] Depend on Fig. 9It can be seen that the content of available Cd in different treatment groups showed an overall downward trend with the increase of days. The content of available Cd in the soil on the 7th and 14th days decreased significantly with the increase of CaFe-LDH@BT addition. The content of available Cd in the treatment group with 1.5% CaFe-LDH@BT addition was the lowest in the same period, which was 29.81% and 41.93% lower than that of the blank control group, respectively. In the experimental groups at 30, 60, and 100 days, the content of available Cd did not decrease in a step-like manner with the increase of addition. The lowest values ​​appeared in the 0.8%, 0.8%, and 0.4% treatment groups, respectively. The content of available Cd in the treatment group with the largest amount of material addition, 1.5% CaFe-LDH@BT, was not the lowest. This may be because the addition of too much CaFeLDH@BT led to aggregation between each other, resulting in a reduction in active sites that can bind to Cd, resulting in poor passivation effect. In addition, when the addition amount of CaFe-LDH@BT and BT was 0.4%, the content of available Cd in the soil of the CaFe-LDH@BT treatment group decreased by 1.23%, 20.73%, 0.62%, 0.87% and 26.11% compared with the BT treatment group at 7, 14, 30, 60 and 100 days, respectively. On the 100th day, the content of available Cd in the soil with 0.4% CaFe-LDH@BT addition reached the lowest value of 0.58 mg / kg in the whole experiment, which was 57.65% lower than that of the blank control group. It can be seen that the decrease in the content of available Cd in the soil is not proportional to the addition amount of CaFe-LDH@BT, and the addition amount of 0.4% CaFe-LDH@BT can most effectively passivate the available Cd in the soil.

[0163] 3.2 Effect of CaFe-LDH@BT on the storage form of Cd in soil:

[0164] Once heavy metals enter the soil, they are difficult to degrade and can only be converted from one form to another. Therefore, converting the more toxic form of heavy metals into a less toxic form is an important remediation measure for soil contaminated by heavy metals (Wang et al., 2021). In this study, Cd in the soil was divided into weak acid extraction state (F1), reducible state (F2), oxidizable state (F3) and residual state (F4). The BCR four-step extraction method was used to extract Cd in the soil in four consecutive steps (Koue et al., 2020). The effects of BT and CaFe-LDH@BT on the occurrence forms of Cd in the soil at 7, 14, 30, 60 and 100 days were studied.

[0165] Depend on Fig.10It can be seen that after the application of CaFe-LDH@BT and BT, the proportion of weakly acid extractable (F1) and reducible (F2) Cd in the soil gradually decreased with the increase of application days, and was converted into a less active and more stable residual state (F4). On the 7th and 14th days, the Cd in the soil of the treatment group mainly existed in the form of weakly acid extractable and reducible states, with the proportions of the two being between 82.39% and 83.76% on the 7th day and between 82.66% and 83.52% on the 14th day. On the 30th day, the proportion of weakly acid extractable and reducible Cd in the soil of the treatment group decreased to between 55.09% and 59.71%, a decrease of 24.05% to 27.3% compared with the 7th day, and the proportion decreased to 47.35% to 53.92% on the 60th day, a decrease of 29.84% to 35.04% compared with the 7th day. On the 100th day, the proportion of weakly acid-extractable and reducible Cd in the soil of the treatment group was between 31.48% and 44.14%, which was a decrease of 39.62% to 50.91% compared with the 7th day. The proportion of residual Cd in the treatment group was between 44.80% and 52.04%, which was a significant increase compared with the 7th, 14th, 30th, and 60th days.

[0166] On the 100th day, the treatment group with 0.4% CaFe-LDH@BT addition had the best passivation effect. The proportion of weakly acid treated and reducible Cd was reduced by 14.94% compared with the blank control group, and was reduced by 8.31% compared with the treatment group with 0.4% BT addition. The proportion of residual Cd increased by 12.07% compared with the blank control group, and increased by 4.92% compared with the treatment group with 0.4% BT addition. It can be seen that the passivation effect of CaFe-LDH@BT is better than that of BT. This is because the specific surface area of ​​CaFe-LDH@BT obtained after loading CaFe-LDH has been significantly increased, and it has more active sites and functional groups, which enhances the passivation effect on Cd in the soil, and can convert more highly active forms of Cd into low-activity residual states.

[0167] 3.3 Effect of CaFe-LDH@BT on tomato plants:

[0168] 3.3.1 Effect of CaFe-LDH@BT on tomato plant biomass:

[0169] Excessive heavy metals can inhibit plant growth and cause a decrease in biomass. This is because heavy metals interfere with the physiological and metabolic processes of plants, including oxidative stress, toxic genetics, programmed cell death, and disorders of various physiological processes. Tomato plants were harvested on the 100th day. The fresh weight of the aboveground and underground parts of tomato plants in different treatment groups was as follows: Fig.11 shown.

[0170] Depend on Fig.11 It can be seen that there are certain differences in the fresh weight of the aboveground part of tomato plants in different treatment groups. Among them, the fresh weight of the aboveground part of tomato plants in the treatment group with 0.4% CaFeLDH@BT addition is the largest, which is 52.62g / pot, and there are significant differences compared with other treatment groups (p<0.05), which is 31.02% higher than the fresh weight of the treatment group with 0.4% BT addition; and the treatment groups with CaFe-LDH@BT addition higher than 0.4% showed an inhibitory effect on the fresh weight of tomato plants, and their fresh weight was lower than that of the blank control group without any material added. Among them, the fresh weight of tomato plants in the treatment group with 1.5% CaFe-LDH@BT addition was 55.66% lower than that of the blank control group. This may be due to the excessive application of CaFe-LDH@BT leading to nutritional imbalance in the soil and an increase in soil pH. The increase in pH will reduce the relative nutrition in the soil, thereby inhibiting the growth and development of the plants.

[0171] The dry weight of aboveground and underground parts of tomato plants in different treatment groups Fig.12 As shown in the figure, the trends of the dry weights of the aboveground and underground parts of tomato plants in different treatment groups are relatively consistent. The dry weight of the aboveground part of the plants in the 0.4% CaFe-LDH@BT addition treatment group was the highest, reaching 5.44 g / pot, which was 20.73% higher than the dry weight of the aboveground part of the blank control group, and this treatment group was significantly different from the other treatment groups (p<0.05). The dry weights of the aboveground and underground parts of tomato plants in the 1.5% CaFe-LDH@BT addition treatment group were the smallest, only 1.97 g / pot and 0.18 g / pot, which were 54.40% and 28.85% lower than those of the blank control group, respectively. The dry weight of the aboveground part of the treatment group with 0.4% CaFe-LDH@BT addition was the largest, at 5.44 g / pot, which was 26.15% higher than the blank control group without any material added, 41.38% higher than the treatment group with 0.4% BT addition, and 63.85% higher than the dry weight of the treatment group with 1.5% CaFe-LDH@BT addition, where plant growth was inhibited.

[0172] In summary, the more CaFe-LDH@BT is added, the better the effect is. In Cd-contaminated soil, compared with the blank control group without any material added, 0.4% CaFe-LDH@BT has the best effect on increasing the fresh weight and dry weight of plants, while the addition of CaFe-LDH@BT higher than 0.4% will inhibit the growth of plants; at the same addition of 0.4%, the plants in the CaFe-LDH@BT treatment group have higher fresh weight and dry weight than those in the BT treatment group. In addition, from an economic point of view, the addition of 0.4% CaFe-LDH@BT is also more helpful in saving costs.

[0173] 3.3.2 Effects of CaFe-LDH@BT on plant height and root length of tomato plants:

[0174] Heavy metals in the soil have a certain inhibitory effect on the growth and development of tomato plants. Heavy metals can interfere with the physiological processes of plants, such as photosynthesis, respiration and nutrient absorption, thereby limiting plant growth and reducing plant height. They can also accumulate in the roots, stems, leaves and fruits of plants, interfering with the cell structure and function of plants, leading to cytotoxicity and tissue damage, and slowing plant growth.

[0175] High concentrations of Cd will interfere with the absorption and transport of nutrients by plant roots. Cd will compete with some essential nutrients for plants (such as calcium, iron, magnesium, etc.) for adsorption sites, inhibiting the absorption of nutrients. In addition, high concentrations of Cd will also cause structural damage to plant root tissues, such as thickening of root cell walls. These changes may reduce the effective absorption area of ​​plant roots and the absorption capacity of root hairs. Fig.13 shown.

[0176] Depend on Fig.13 (a) It can be seen that the height of tomato plants in different treatment groups has certain differences, 0.8%

[0177] The tomato plants in the CaFeLDH@BT addition treatment group were the tallest, reaching 33.27cm / pot, which was 47.02% higher than the blank control group without any materials added; the tomato plants in the 0.4% CaFe-LDH@BT addition treatment group were the second tallest, which was 32.70% higher than the blank control group without any materials added, and there was no significant difference between the tomato plants in the 0.8% CaFe-LDH@BT addition treatment group (p<0.05). In addition, in the Cd-contaminated soil, the 0.4% CaFeLDH@BT addition treatment group increased the plant height by 30.74% compared with the 0.4% BT addition treatment group. It can be seen that BT has a better repair effect than the original BT after loading CaFe-LDH. The growth of tomato plants in the 1.5% CaFe-LDH@BT addition treatment group was significantly inhibited, and its plant height was only 12.47cm / pot, which was 44.90% lower than the blank control group without any materials added.

[0178] Depend on Fig.13(b) It can be seen that, except for the treatment group with 1.5% CaFe-LDH@BT addition, the root lengths of the remaining treatment groups are arranged in a stepped manner. The root lengths of tomato plants in different treatment groups are arranged from small to large as CK < F0.2% < BT0.4% < F0.4% < F0.8%. The root length of tomato plants in the treatment group with 1.5% CaFe-LDH@BT addition is only 5.4 cm / pot, which is 4.09% lower than that of the blank control group without adding any materials. Compared with the BT treatment group with the same addition amount of 0.4%, the root length of tomato plants in the treatment group with 0.4% CaFe-LDH@BT addition increased by 15.59%, showing a better repair effect. Although the root length of tomato plants in the treatment group with 0.8% CaFe-LDH@BT addition reached the highest value, it only increased by 2.87% compared with the root length of tomato plants in the treatment group with 0.4% CaFe-LDH@BT addition, and there was no significant difference between the two (p < 0.05). Therefore, it can be considered that the application effects of the two are basically the same.

[0179] 3.3.3 Effects of CaFe-LDH@BT on Cd in tomato plants:

[0180] After soil remediation materials and heavy metal passivators are added to the soil, they reduce the toxicity, availability and mobility of heavy metals in the soil through surface adsorption, super-stable mineralization, interlayer anion coordination, chelation, anion exchange, etc., greatly reducing their adverse effects on plants. The Cd contents in the roots, stems, leaves and fruits of tomato plants in different treatment groups are as Fig.14 shown.

[0181] From Fig.14 (a), it can be seen that the Cd content in the roots of tomato plants in the blank control group without adding any materials is the highest, which is 4.46 mg / kg. The Cd content in the roots of tomato plants in the treatment group with 0.4% CaFe-LDH@BT addition is the lowest, which is 3.26 mg / kg, a decrease of 26.91% compared with the blank control group. In addition, the Cd content in the roots of tomato plants in the BT treatment group with 0.4% addition is 3.53 mg / kg, while the Cd content in the roots of tomato plants in the treatment group with 0.4% CaFe-LDH@BT addition is 3.26 mg / kg, a decrease of 8.28% compared with this level, showing a better repair effect. After the addition amount of CaFe-LDH@BT exceeds 0.4%, the fixation effect on Cd in the soil gradually weakens, and the Cd content in the roots of tomato plants gradually increases. The Cd contents in the roots of tomato plants in different treatment groups are all lower than those in the blank control group.

[0182] From Fig.14(b) It can be seen that the Cd content in the stems of tomato plants in different treatment groups is arranged in a stepped manner. The Cd content in the stems of tomato plants in the blank control group without any material added is the highest, reaching 2.68 mg / kg, and the Cd content in the stems of tomato plants in the 1.5% CaFeLDH@BT addition treatment group is the lowest, at 0.88 mg / kg, which is 67.16% lower than that in the control group. The Cd content in the stems of tomato plants in the 0.4% BT treatment group is 1.89 mg / kg, and the Cd content in the roots of tomato plants in the 0.4% CaFe-LDH@BT treatment group is 28.04% lower than this level, at 1.36 mg / kg, showing a better repair effect. In addition, there is no significant difference in the Cd content in the stems of tomato plants between the 0.4% and 0.8% CaFe-LDH@BT addition treatment groups (p<0.05), and the difference in the Cd content in the stems of tomato plants between the two is only 0.06 mg / kg.

[0183] Depend on Fig.14 (c) It can be seen that the Cd content in the leaves of tomato plants in different treatment groups is arranged in a stepped manner. The Cd content in the leaves of the blank control group without any material added is the highest, reaching 4.52 mg / kg, and the Cd content in the leaves of tomato plants in the 1.5% CaFeLDH@BT addition treatment group is the lowest, at 2.27 mg / kg, which is 49.78% lower than that of the BT treatment group. At the same addition of 0.4%, the Cd content in the leaves of the CaFe-LDH@BT treatment group is 11.68% lower than that of the BT treatment group, showing a better repair effect.

[0184] Depend on Fig.14 (d) It can be seen that the Cd content in the fruit of the blank control group without any material added was the highest, which was 0.80 mg / kg, and the Cd content in the fruit of the tomato plants in the treatment group with 1.5% CaFe-LDH@BT addition was the lowest, which was 0.40 mg / kg, which was 50.00% lower than that of the blank control group. Except for the blank control group and the treatment group with 1.5% CaFe-LDH@BT addition, there was no significant difference in the Cd content in the fruit of the tomato plants in the other treatment groups. Consistent with the previous results in roots, stems, and leaves, at the same addition of 0.4%, CaFe-LDH@BT still showed a better effect than BT, reducing the Cd content in tomato fruits by 23.08%.

[0185] In summary, the Cd content in different parts of tomato plants in different treatment groups was not proportional to the added amount, but the addition of CaFe-LDH@BT effectively reduced the Cd content in different parts of tomato plants. In addition, the Cd content in roots, stems, leaves, and fruits of tomato plants in the treatment group with 0.4% CaFeLDH@BT addition was lower than that in the treatment group with 0.4% BT addition. CaFe-LDH@BT in different treatment groups can reduce Cd in tomato plants more effectively than original BT. Therefore, CaFe-LDH@BT has broad application prospects.

[0186] 3.3.4 Effects of CaFe-LDH@BT on Cd transport and aboveground accumulation coefficient in tomato plants:

[0187] Tomato has a certain enrichment effect on Cd, so the actual restoration effect of CaFe-LDH@BT was studied by measuring the Cd transport coefficient and aboveground enrichment coefficient in tomato plants. Table 5 below shows the transport and aboveground enrichment coefficients of Cd in tomato plants in different treatment groups.

[0188] Table 5 Translocation and aboveground accumulation coefficient of Cd in tomato plants under different treatments

[0189]

[0190] As shown in Table 5, the application of CaFe-LDH@BT reduced the Cd transport coefficient and aboveground enrichment coefficient in tomato plants, indicating that CaFe-LDH@BT effectively passivated Cd in the soil and reduced the enrichment of Cd in tomato plants.

[0191] The above description is only the preferred embodiment of the present application and is not intended to limit the present application. For those skilled in the art, the present application may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application shall be included in the protection scope of the present application.

Claims

1. Use of bentonite-supported calcium iron layered double hydroxide in at least one of the following (1)-(3): (1) Increase the fresh weight and dry weight of tomato plants grown in cadmium-contaminated soil; (2) Increase plant height and root length of tomato plants grown in cadmium-contaminated soil; (3) passivation of cadmium in tomato plants grown in cadmium-contaminated soil; The bentonite-loaded calcium iron layered double hydroxide is prepared by the following method: Bentonite, FeCl 3· 6H2O and CaCl2 are dissolved in deionized water, and Na2CO3 and NaOH solutions are added under stirring to adjust the pH to 11-13 to obtain a solid-liquid mixture. After the reaction, the precipitate is filtered to obtain a precipitate, which is washed with deionized water to neutrality, dried, and ground to obtain bentonite-loaded calcium iron layered double hydroxide.

2. The use according to claim 1, characterized in that: Passivating cadmium in tomato plants grown in cadmium-contaminated soil specifically reduces the cadmium content in roots, stems, leaves and fruits of tomato plants grown in cadmium-contaminated soil.

3. The use according to claim 1, characterized in that: Bentonite, FeCl 3· The ratio of the added amounts of 6H2O, CaCl2 and water is (3-5) g: (0.02-0.04) mol: (0.10-0.15) mol: (250-350) mL.

4. The use according to claim 1, characterized in that: The concentrations of Na2CO3 and NaOH solutions are both 0.4-0.6 mol / L.

5. The use according to claim 1, characterized in that: The volume ratio of Na2CO3 and NaOH solution is 1:2-4.

6. The use according to claim 1, characterized in that: The reaction temperature is 70-90°C and the reaction time is 16-20h.

7. The use according to claim 1, characterized in that: The specific methods of application are: The bentonite-loaded calcium iron layered double hydroxide is applied to cadmium-contaminated soil for passivation treatment, and the applied amount is 3-5 g of bentonite-loaded calcium iron layered double hydroxide per kilogram of soil.